2016
DOI: 10.1159/000444880
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Protein Kinase A in Anxiety Behaviors

Abstract: This review focuses on the genetic and other evidence supporting the notion that the cyclic AMP (cAMP) signaling pathway and its mediator, the protein kinase A (PKA) enzyme, which respond to environmental stressors and regulate stress responses, are central to the pathogenesis of disorders related to anxiety. We describe the PKA pathway and review in vitro animal studies (mouse) and other evidence that support the importance of PKA in regulating behaviors that lead to anxiety. Since cAMP signaling and PKA have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 185 publications
(207 reference statements)
0
13
0
Order By: Relevance
“…Recent work has suggested that activation of the IP receptor, a cAMP-dependent PKA pathway, may be sufficient to drive stress responses in vivo (61). Stimulation of this pathway leads to activation of CRE (cAMP-responsive elements) binding proteins in the nucleus to synthesize new proteins that alter fear learning and memory formation (61). Increased expression of prostacyclin also appeared to exert detrimental effects on other cognitive tests.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has suggested that activation of the IP receptor, a cAMP-dependent PKA pathway, may be sufficient to drive stress responses in vivo (61). Stimulation of this pathway leads to activation of CRE (cAMP-responsive elements) binding proteins in the nucleus to synthesize new proteins that alter fear learning and memory formation (61). Increased expression of prostacyclin also appeared to exert detrimental effects on other cognitive tests.…”
Section: Discussionmentioning
confidence: 99%
“…DL PA is significantly lower in depressed compared with non‐depressed COPD patients, and anxiety is highly prevalent among asthma patients, where it is associated with more exacerbations, more hospital readmissions, and poorer asthma control . The molecular mechanisms responsible for anxiety are not well understood and might involve abnormal neural processing of stimuli . Therefore, it is possible that asthma patients avoid exercise for fear of triggering symptoms, which leads to a sustained overall aversion to exercise .…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that impaired generation and functional integration of adult-born DG neurons as well as dys-regulation of cAMP/PKA-signaling play a significant role in the pathophysiology of neuropsychiatric and neurodegenerative disorders such as anxiety, depression, and Alzheimer’s disease 34 38 . It will be interesting to explore if and how dys-regulation of SOX11 phosphorylation contributes to those pathologies.…”
Section: Discussionmentioning
confidence: 99%